A nationwide, cross‐sectional survey on unusual sleep postures and sleep‐disordered breathing‐related symptoms in people with Down syndrome. Issue 7 (5th April 2017) - Kuroda, H.; Sawatari, H.; Ando, S.; Ohkusa, T.; Rahmawati, A.; Ono, J.; Nishizaka, M.; Hashiguchi, N.; Matsuoka, F.; Chishaki, A.
Abstract: Background: People with Down syndrome (DS) often have sleep‐disordered breathing (SDB). Unusual sleep postures, such as leaning forward and sitting, are observed in people with DS. This study aimed to clarify the prevalence of unusual sleep postures and their relationships with SDB‐related symptoms (SDB‐RSs), such as snoring, witnessed apnoea, nocturnal awakening and excessive daytime sleepiness. Methods: A questionnaire, including demographic characteristics and the presence of unusual sleep postures, as well as SDB‐RSs, was completed by 1149 parents of people with DS from Japan. Results: Unusual sleep postures were recorded in 483 (42.0%) people with DS. These participants were significantly younger and had a history of low muscle tone more frequently than people without unusual sleep postures. In all ages, the leaning forward posture was more frequent than sitting. People with DS with unusual sleep postures suffered from SDB‐RSs. Those who slept in the sitting posture had more frequent SDB‐RSs than did those who slept with the leaning forward posture. Snoring, witnessed apnoea and nocturnal awakening were observed in 73.6, 27.2 and 58.2% of participants, respectively. Snoring increased with aging. Witnessed apnoea was more common in males and in those with hypothyroidism than in females and in those without hypothyroidism. Conclusions: Our study shows that there is a close relationship between unusual sleep postures and SDB‐RSs. We recommend that all people with DS with unusual sleep postures should be checked for the presence of SDB.